Diabetes and hypertension are associated with lowered cognitive performance among middle-aged Brazilian adults: cross-sectional analyses nested in the longitudinal Pró-Saúde study - Passos, Valéria Maria de Azeredo (2021)
BACKGROUND: Cardiovascular risk factors are frequently associated with lowered cognitive performance among elderly people, but rarely among middle-aged adults. OBJECTIVES: To investigate associations between cardiovascular risk factors (age, physical inactivity, smoking, alcohol use, hypertension and diabetes) and lower cognitive performance among middle-aged (45-64 years) Brazilian adults. DESIGN AND SETTING: Cross-sectional study nested within the Pró-Saúde cohort. From 2,876 baseline study participants (1999), we randomly selected 488 participants and gave them validated and standardized cognitive tests (2012). METHODS: We used multiple linear and logistic regression analyses to detect associations of cardiovascular risk factors with crude scores in cognitive tests on memory (word test) and executive function (verbal fluency tests), and with overall cognitive performance scores, respectively. RESULTS: All cognitive test scores presented statistically significant inverse associations with age and direct associations with education. There was no association between lower cognitive performance and smoking or alcohol use. In both 1999 and 2012, after adjusting for sex, age and schooling, being physically active was inversely associated with lower performance regarding late memory. For individuals with diabetes in 1999, there was an association with lower performance regarding executive function, while there was a borderline association for those reporting it only in 2012. Having a diagnosis of hypertension since 1999 was associated with lower performance regarding both memory and executive functions, while reporting hypertension in 2012 was associated with lower performance regarding executive function. CONCLUSIONS: Aging, low schooling and cardiovascular risk factors may represent life course disadvantages associated with cognitive decline even among middle-aged Brazilian adults.